The Reduction of Inequality in the Society Through Buddhist Ethics of People in Khonkaen - Saengool, Komgris; Thongpan, Suwin; Leeka, Jaras; Baokham, Natthaphon (Journal of Graduate MCU KhonKaen Campus, 2025)
Research objectives: 1) To study inequality among the people of Khon Kaen Province, 2) To study the principles of Buddhist ethics used to reduce inequality in society, 3) To study the reduction of inequality in society using the principles of Buddhist ethics among the people of Khon Kaen Province. This is a qualitative research. The research tools include in-depth interviews and focus group discussions. Key informants include 10 social academics, 10 government officials, and 10 citizens. The data were analyzed using descriptive analysis based on the inductive approach. The research results were as follows: 1. Reducing social inequality with Buddhist ethics of the people of Khon Kaen Province includes using the Dharma of the World, the Brahmaviharas, and the Sanghavatthu to train and instill morality and ethics in people in society at the individual level to reduce social inequality in 3 areas: 1) Quality of life, including access to medical facilities, medical personnel services, knowledge services, public transportation, safety of life and property, and budget allocation. 2) Economy, including poverty, access to capital, and access to government welfare. 3) Education, including access to educational resources, educational opportunities, and educational equipment. 2. Buddhist ethics used to reduce inequality in society are: 1) Dharma Lokapãla, consisting of shame and fear of sin; 2) Brahmavihãra, consisting of love, compassion, rejoicing and neutrality; 3) Sanghavatthu 4, consisting of giving, speaking the right thing, being consistent and doing good for society. 3. Reducing social inequality with Buddhist ethics of the people of Khon Kaen Province includes using the Dharma of the World, the Brahmaviharas, and the Sanghavatthu to train and instill morality and ethics in people in society at the individual level to reduce social inequality in 3 areas: 1) Quality of life, including access to medical facilities, medical personnel services, knowledge services, public transportation, safety of life and property, and budget allocation. 2) Economy, including poverty, access to capital, and access to government welfare. 3) Education, including access to educational resources, educational opportunities, and educational equipment.